2003
DOI: 10.1071/fp03129
|View full text |Cite
|
Sign up to set email alerts
|

Copper-induced inhibition of photosynthesis: limiting steps of in vivo copper chlorophyll formation in Scenedesmus quadricauda

Abstract: The in vivo substitution of Mg2+ in chlorophyll by heavy metals is an important damage mechanism in heavy metal-stressed plants that leads to an inhibition of photosynthesis. In photosynthetic organisms with LHC II antennae, the in vivo substitution of Mg2+ by Cu2+ occurs particularly readily under low irradiance with a dark phase — a phenomenon referred to as 'shade reaction'. In the present study the limiting steps of the shade reaction were investigated with synchronised cultures of the chlorococcal green a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 20 publications
4
48
0
Order By: Relevance
“…ions, followed by photosynthesis and respiration. In contrast, Miao et al (2005) using batch cultures and environmentally relevant Cu levels (pCu 13 to pCu 5.6) suggested that phytoplankton growth rates were as sensitive as F v /F m (equivalent to U M ) for the detection of Cu toxicity, whereas Kupper et al (2003) observed that toxic Cu levels impaired photosynthesis faster than cell division in Scenedesmus quadricauda cultures. We believe that some of the literature controversial effects of high Cu in U M might be because of whether batch versus semi-continuous cultures were used, as well as the time of sampling.…”
Section: Effects Of High Cumentioning
confidence: 79%
“…ions, followed by photosynthesis and respiration. In contrast, Miao et al (2005) using batch cultures and environmentally relevant Cu levels (pCu 13 to pCu 5.6) suggested that phytoplankton growth rates were as sensitive as F v /F m (equivalent to U M ) for the detection of Cu toxicity, whereas Kupper et al (2003) observed that toxic Cu levels impaired photosynthesis faster than cell division in Scenedesmus quadricauda cultures. We believe that some of the literature controversial effects of high Cu in U M might be because of whether batch versus semi-continuous cultures were used, as well as the time of sampling.…”
Section: Effects Of High Cumentioning
confidence: 79%
“…29,2010with increasing concentration over the range of 20 to 80 nM of Cu. Copper has been shown to inhibit photosynthesis through substitution for Mg 2þ in chlorophyll [30], but Cd may act differently to inhibit photosynthesis, such as by binding to a Ca site in Photosystem II [17].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of chlorophyll content induced by excess copper in chloroplasts has been observed in a variety of species such as Ceratophyllum demersum L., 23 Empetrum nigrum, 24 Brassica pekinensis Rupr, 25 and Triticum aestivum L. 26 It has been proposed that Cu at high concentrations affects plants via two main mechanisms: interference with enzymes associated with chlorophyll biosynthesis and the changes in protein composition of photosynthetic membranes. 27,28 In addition, Cu-induced Fe deficiency 29 and the displacement by Cu of the Mg required for chlorophyll biosynthesis 30 have been proposed as possible additional damage mechanisms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%